2018
DOI: 10.1177/0146167218775690
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Clothing Does Not Make the Object: ERP Evidences That Cognitive Objectification is Driven by Posture Suggestiveness, Not by Revealing Clothing

Abstract: Recent research found that sexualized bodies are visually processed similarly to objects. This article examines the effects of skin-to-clothing ratio and posture suggestiveness on cognitive objectification. Participants were presented images of upright versus inverted bodies while we recorded the N170. We used the N170 amplitude inversion effect (larger N170 amplitudes for inverted vs. upright stimuli) to assess cognitive objectification, with no N170 inversion effect indicating less configural processing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 63 publications
1
30
1
1
Order By: Relevance
“…Therefore, it is crucial to continue studying this phenomenon, but with different methods and measures. For instance, a promising way to assess sexual objectification comes from studies investigating it at the neurophysiological level (e.g., [48,83,84]). In particular, empirical research has pointed to the N170, which is a negative amplitude Event Related Potential evoked by visual stimuli at occipitotemporal regions, approximately 140 to 200 ms after stimulus onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is crucial to continue studying this phenomenon, but with different methods and measures. For instance, a promising way to assess sexual objectification comes from studies investigating it at the neurophysiological level (e.g., [48,83,84]). In particular, empirical research has pointed to the N170, which is a negative amplitude Event Related Potential evoked by visual stimuli at occipitotemporal regions, approximately 140 to 200 ms after stimulus onset.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the amplitude of N170 has been shown to be increased for images of bodies presented upside down, as compared to upright but, interestingly, this increase in amplitude did not emerge for objects [86]. Recently, Bernard and colleagues [48,83,84] showed that non-sexualized bodies presented larger N170 amplitudes when viewed upside-down than in upright positions, whereas bodies with sexually suggestive posturer failed to evoke a stronger N170 response when presented upside-down. This result suggests that the amplitude of the inversion in N170 might be a useful signal that stimuli are processed configurally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…globally whereas they rely on a more local, piecemeal processing when viewing images of sexualized bodies and ordinary objects, and this cognitive objectification occurs at both neural (e.g., Bernard, Content, Deltenre, & Colin, 2018;Bernard, Hanoteau et al, 2018;Bernard, Rizzo et al, 2018) and behavioral levels (Bernard, Gervais, Allen, Campomizzi, & Klein, 2015;Bernard, Gervais, Allen, Campomizzi, & Klein, 2012;Bernard, Gervais, Allen, Delmée, & Klein, 2015;Civile & Obhi, 2016). In accordance with feminist scholars who posited that objectification is related to a reduction of others to their sexual body parts (e.g., Bartky, 1990), this line of research shows that sexualized bodies are cognitively reduced to their parts akin to objects (for a review, see .…”
mentioning
confidence: 99%
“…Fasoli et al (2018) found that the women in the sexualized revealing condition were perceived more as sexual objects in comparison with the women in the revealing condition, followed by the women in the nonrevealing condition, thereby suggesting that people perceive women as being sexual objects to a greater extent when targets are both wearing revealing clothing and displaying suggestive postures. In a related manner, another recent study manipulated revealing clothing and posture suggestiveness while assessing the neural correlates of the early visual processing of sexualized people (Bernard, Hanoteau, et al, 2018). Specifically, the authors manipulated revealing clothing and posture suggestiveness and examined whether revealing clothing, posture suggestiveness, or both cause bodies to be processed less configurally and more analytically, that is, similarly to the way most objects are perceived (Maurer, Le Grand, & Mondloch, 2002).…”
mentioning
confidence: 99%